Getting acquainted with accounting - Carey, John L. (Houghton Mifflin, 1977)
This book explores the why of accounting from a broad perspective for the introductory student. Such topics as the end uses of accounting and their relation to economic and social problems reflect the author's conviction that the student's conceptual knowledge is at least as important as his technical skills.